Persepsi Kepala Sekolah Terhadap Kompetensi Guru Dalam Proses Pembelajaran Kurikulum Merdeka Belajar - Shelty D.M Sumual; Paulus Tuerah; Henny B.A Kiriweno; Dafrosa Pandey (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the principal's perception of teacher competence in the learning process of the independent curriculum. This research method uses quantitative descriptive research, with the survey method. From the data obtained, it can be concluded that elementary schools in Tomohon City can be categorized as schools that are ready to implement the independent learning curriculum, this can be seen based on the results of the study, namely the principal's perception of teacher competence in the learning process of the independent learning curriculum based on competency indicators, both indicators of pedagogical competence, social competence, professional competence and personality competence, all four indicators are in the very good category according to the principal's perception.